1995
DOI: 10.3109/02770909509089499
|View full text |Cite
|
Sign up to set email alerts
|

Do Both Paternal and Maternal Smoking Influence the Prevalence of Childhood Asthma? A Study into the Prevalence of Asthma in Children and the Effects of Parental Smoking

Abstract: Asthma is one of the commonest of chronic illnesses affecting children. Parental smoking has been considered to have an effect on this. In an attempt to clarify the relationship between parental smoking and the prevalence of childhood asthma we interviewed parents of 97.5% of the children aged 3-11 years registered with a large urban British general practice. We found a lifetime prevalence of asthma of 19.6%, 23.2% of boys and 15.9% of girls. Asthma was more common, 37.6%, in children who also had eczema. Pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 15 publications
1
6
0
1
Order By: Relevance
“…Other symptoms such as night time coughing with no cold also increased when the children were exposed to passive smoking, although this effect was smaller. Our results are similar to those of Kay et al ,21 who found that parental smoking appeared to increase the prevalence of asthma, especially when both parents smoked.…”
Section: Discussionsupporting
confidence: 92%
“…Other symptoms such as night time coughing with no cold also increased when the children were exposed to passive smoking, although this effect was smaller. Our results are similar to those of Kay et al ,21 who found that parental smoking appeared to increase the prevalence of asthma, especially when both parents smoked.…”
Section: Discussionsupporting
confidence: 92%
“…We also showed that low-income families were more likely to contain two parents who smoked. A number of overseas 4,20,21 and Australian 22,23 studies have also reported that parents who smoke are drawn disproportionately from disadvantaged groups.…”
Section: Discussionmentioning
confidence: 99%
“…49 Finally, given the now large body of literature that documents a relationship between parental smoking and infant health, it seems appropriate that we infer from the findings of our study and suggest that infants of parents who smoked, especially those from disadvantaged backgrounds, were at increased risk of experiencing higher mortality and morbidity for childhood conditions related to passive smoking, such as respiratory illness, middle ear effusion, SIDS, and reduced ventilatory function. [2][3][4][5][6][7][8][9][10][11][12] Given available evidence, we could also assume that the infants in this study's sample who were exposed to ETS will disproportionately experience adverse health consequences in later life, [13][14][15][16] and may themselves take up smoking in adulthood. [17][18][19] In short, we can see in our data the genesis of many adult socio-economic health differentials.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Park and Kim [33] deÿne a non-smoker as a person who had not smoked for one month prior to the interview, whereas, O'Connor et al [34] deÿne current cigarette smoking as currently smoking at least one cigarette per day or having quit such a habit within the past twelve months. Some papers did not even pro er a deÿnition of a smoker [35]. This nebulous deÿnition of smoking may contribute to the considerable variation shown in the results from otherwise comparatively analogous studies.…”
Section: Deÿnition Of Etsmentioning
confidence: 99%